Potentiality of Digested Rotten Guava Medium (DRGM) in Replacement of Kosaric Medium (KM): Perspective of Spirulina platensis culture (American Journal of Multidisciplinary Research and Innovation, 2022)
This study was conducted to evaluate the culture potentiality and growth performance of Spirulina (Spirulina platensis) in supernatant digested rotten guava (DRG) in replacement of Kosaric Medium (KM). The Spirulina was inoculated to grow in digested rotten guava media (DRGM) (treatments) with the addition of 9.0 g/L NaHCO3 and micronutrients and KM for a period of 14 days. The cell weight of spirulina was attained a maximum of 12.43±0.20 mg/L (dry wt. basis) in KM followed by 0.818 ± 0.003, 0.815 ± 0.0015 and 0.809± 0.0012 mg/L in supernatant of 60 (T1), 20 (T2) and 40% DRGM (T3), respectively on the 10th day of culture. The cell weight of spirulina grown in these media had highly significant (P